2015
DOI: 10.1111/aas.12534
|View full text |Cite
|
Sign up to set email alerts
|

Effects of remifentanil on esophageal motility: a double‐blind, randomized, cross‐over study in healthy volunteers

Abstract: Remifentanil induces dysfunction of esophageal motility; this may contribute to the elevated risk of regurgitation and aspiration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 30 publications
4
26
0
Order By: Relevance
“…We report data from 11 healthy young (23.3 Ϯ 3.1 yr old) participants (7 men and 4 women) who were previously enrolled in a double-blind, randomized, placebo-controlled, cross-over study of opioid drugs (27) and had provided informed consent. In this previous publication, we reported pharmacodynamic effects at two time points, 15 and 30 min following commencement of remifentanil infusion.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We report data from 11 healthy young (23.3 Ϯ 3.1 yr old) participants (7 men and 4 women) who were previously enrolled in a double-blind, randomized, placebo-controlled, cross-over study of opioid drugs (27) and had provided informed consent. In this previous publication, we reported pharmacodynamic effects at two time points, 15 and 30 min following commencement of remifentanil infusion.…”
Section: Methodsmentioning
confidence: 99%
“…reported during exposure to remifentanil (27). Specifically, we used mechanical states analysis to deduce the duration of "pause" of neural activation of the CP muscle (23,24).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ratuapli et al were also able to demonstrate retrospective in a comparative study an opioid-induced EGJ outflow obstruction and spastic peristalsis in patients with continued opioid therapy compared to patients with at least 24 hours without pain therapy (28). A double-blind, cross-over study in healthy volunteers from Sweden showed that for example remifentanil induces dysfunction of esophageal motility with EGJ relaxation and distance latency decreasing (29). In the present work, the influence was not explicitly investigated.…”
Section: Discussionmentioning
confidence: 57%
“…These studies report aspiration of saliva and nasal secretions in 10-100% of healthy persons, 70% of patients with depressed consciousness, 71% of patients with community-acquired pneumonia, and 100% of patients with chronic sinusitis and asthma. Saliva aspiration has also been found in 48% of patients under sedation with anesthetics [5], and aspiration of gastric contents was found in 8.3% of patients who did not vomit during surgery under general anesthesia [6]. With regard to saliva aspiration when awake, videoendoscopy carried out on 81 patients undergoing otolaryngological examination who did not complain of dysphagia showed saliva aspiration in two cases [7].…”
Section: Introductionmentioning
confidence: 99%